2011
DOI: 10.4066/amj.2011.486
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal scar endometriosis after Caesarean section: a rare entity

Abstract: Scar endometriosis is an uncommon entity. It is often misdiagnosed leading to unnecessary referrals. Gynaecologists and general surgeons must be aware of this entity to avoid discomfort to the patient due to delay in diagnosis. We are presenting a case of scar endometriosis which was misdiagnosed initially. Detailed history of cyclic pain and swelling was the key point for the final diagnosis of scar endometriosis. Medical therapy was ineffective. Surgical excision of mass was the treatment for endometriotic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
0
4
0
9
Order By: Relevance
“…2,12,13 In these patients, the rate of occurrence of pelvic endometriosis is similar to that of other women, and is not regarded as a risk factor for the disease. 14 The incidence of abdominal wall endometriosis (AWE) is rare. The disorder occurs in 0.03-3.5% of cases, and some studies have reported a rate of up to 12%.…”
Section: Introductionmentioning
confidence: 99%
“…2,12,13 In these patients, the rate of occurrence of pelvic endometriosis is similar to that of other women, and is not regarded as a risk factor for the disease. 14 The incidence of abdominal wall endometriosis (AWE) is rare. The disorder occurs in 0.03-3.5% of cases, and some studies have reported a rate of up to 12%.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography, computed tomography (CT), Magnetic resonance imaging (MRI) of the abdomen and pelvis are important to define not only the size of the lesion, but also the degree of involvement of the abdominal wall. MRI's sensitivity for the diagno-VOLUME 17 ISSUE 1, JANUARY-MARCH 2018 Ververidou et al sis of abdominal wall endometriosis is reported up to 71% and its specificity as 82%; it has been suggested that MRI seems to be the best method in preoperative diagnosis as it can be used to evaluate pelvic and extraperitoneal disease [4][5][6] . Fine-needle aspiration (FNA) cytology is generally inconclusive, although it may be of some value in planning surgical approach for the management of cases of scar endometriomas 5. Finally, laparoscopy is the gold standard for evaluating and diagnosing pelvic and peritoneal endometriotic implantations 7 .…”
Section: Discussionmentioning
confidence: 99%
“…9 The incidence of scar endometriosis following hysterotomy is high because the early decidual cell have more pleuripotential capabilities. 10 Elective caesarean section performed before the onset of labor doubles the risk of scar endometriosis. 11 The condition is caused by direct inoculation of endometrial cells into abdominal fascia or subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%